Isolation of Elusive HAsAsH in a Crystalline Diuranium(IV) Complex. Issue 50 (28th October 2015) - Gardner, Benedict M.; Balázs, Gábor; Scheer, Manfred; Wooles, Ashley J.; Tuna, Floriana; McInnes, Eric J. L.; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Liddle, Stephen T.
Abstract: The HAsAsH molecule has hitherto only been proposed tentatively as a short‐lived species generated in electrochemical or microwave‐plasma experiments. After two centuries of inconclusive or disproven claims of HAsAsH formation in the condensed phase, we report the isolation and structural authentication of HAsAsH in the diuranium(IV) complex [{U(Tren TIPS )}2 (μ‐η 2 :η 2 ‐As2 H2 )] (3, Tren TIPS =N(CH2 CH2 NS i Pr i 3 )3 ; Pr i =CH(CH3 )2 ). Complex3 was prepared by deprotonation and oxidative homocoupling of an arsenide precursor. Characterization and computational data are consistent with back‐bonding‐type interactions from uranium to the HAsAsH π*‐orbital. This experimentally confirms the theoretically predicted excellent π‐acceptor character of HAsAsH, and is tantamount to full reduction to the diarsane‐1, 2‐diide form. Abstract : HAsAsH, a molecule first proposed over 200 years ago but never convincingly prepared, has been isolated in a diuranium(IV) complex. Characterization and computational data are consistent with back‐bonding‐type interactions from uranium to the HAsAsH π*‐orbital, thus experimentally confirming the theoretically predicted excellent π‐acceptor character of HAsAsH.